Healthcare use and costs in early breast cancer: a patient-level data analysis according to stage and breast cancer subtype. Issue 6 (24th November 2020) - Brandão, Mariana; Morais, Samantha; Lopes-Conceição, Luísa; Fontes, Filipa; Araújo, Natália; Dias, Teresa; Pereira, Deolinda; Borges, Marina; Pereira, Susana; Lunet, Nuno
Abstract : Background: The cost of breast cancer care rises with higher stage at diagnosis; however, there are no real-world data regarding the cost of care according to breast cancer subtypes. This study aimed to estimate direct medical costs for early breast cancer care in the first 3 years after diagnosis according to subtype and stage, using patient-level data. Methods: Women with newly diagnosed stage I–III breast cancer, admitted in 2012 to a Portuguese cancer centre were prospectively followed within the NEON-BC cohort. The use of health resources was obtained from each patient's clinical and administrative records and costs were computed. Tumours were classified into the classic subtypes (hormone receptor-positive (HR+)/HER2−; HER2-positive (HER2+); triple-negative breast cancer (TNBC)) and surrogate intrinsic subtypes (luminal A-like; luminal B-like; HER2 enriched; basal like). Results: A total of 703 patients were included: 48.9% had stage I, 35.8% stage II and 15.2% stage III breast cancer; 76.4% had HR+/HER2−, 15.9% HER2+ and 7.7% TNBC. Median cost of care was €9215/patient in stage I, €13 019/patient in stage II and €15 011/patient in stage III and €10 540/patient in HR+/HER2−, €11 224/patient in TNBC and €41 513/patient in HER2+ breast cancer. Systemic therapy accounted for 69.2% of the cost of care among patients with HER2+, 12.0% among HR+/HER2− and 7.5% among TNBC patients. Similar differences were observed across surrogate intrinsic subtypes. Conclusions: The cost of early breast cancer care was mainly driven by the tumour subtype and, to a lesser extent, by stage. The median cost of care was fourfold higher among patients with HER2+ tumours compared with those with HR+/HER2− and TNBC. These data provide information for the economic evaluation of innovative treatments for early breast cancer and highlight the weight that targeted systemic therapy might have in the overall cost of care among patients with early breast cancer.